2019
DOI: 10.1039/c8dt04819c
|View full text |Cite
|
Sign up to set email alerts
|

Catechol and 1,2,4,5-tetrahydroxybenzene functionalized cyclodiphosphazane ligands: synthesis, structural studies, and transition metal complexes

Abstract: This paper describes the syntheses of two novel cyclodiphosphazane derivatives and their coordination chemistry with CuI, RuII, RhI, PdII and AuI is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…3 ) (Cass, 2014 ). It was reported that ligands preferred a bridged bidentate mode of coordination (Pandey et al, 2019 ), and Xu ( 2013 ) suggested double (bis-) and triple (tris-) complex formation between catechol and iron (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 90%
“…3 ) (Cass, 2014 ). It was reported that ligands preferred a bridged bidentate mode of coordination (Pandey et al, 2019 ), and Xu ( 2013 ) suggested double (bis-) and triple (tris-) complex formation between catechol and iron (Fig. 4 ).…”
Section: Introductionmentioning
confidence: 90%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Macrocycles embedded with different heteroatoms and donor functionalities can undergo self-assembly with or without metal atoms/ions to form a 1D, 2D or 3Dnetwork with different ring sizes and molecular cavities. [15][16][17] Such molecules with defined cavities can identify and selectively bind cations, anions or neutral molecules of different sizes and shapes including chiral molecules and find a wide range of applications in supramolecular chemistry, 18 materials science 19,20 and drug delivery. 21,22 Molecules such as crown ethers, 23 cyclodextrins, 24 cryptands, 25 calixarenes 26 and resorcin [4]arenes 27,28 have offered impressive model structures for molecular recognition, noncovalent-bond interactions and self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…The recent interest to design phosphorus based ligands appended with pyridine or nitrogen heterocycles and study their group 11 coordination chemistry, in particular copper(I) chemistry is due to their rich structural and photo luminescent properties,, non‐toxicity, functional materials and catalytic applications . Gold(I) complexes are also widely studied because of their strong emission and interesting photophysical properties associated with their aurophilicity .…”
Section: Introductionmentioning
confidence: 99%